2021
DOI: 10.2174/1566524020666200427101231
|View full text |Cite
|
Sign up to set email alerts
|

Active Immunotherapy with 12-mer Aβ1-42-like Assembly Vaccine Shows Efficacy in Aged 3×Tg-AD Mice

Abstract: Background: Alzheimer's disease (AD) is the most common progressive neurodegenerative disorder, characterized by senile plaques and neurofibrillary tangles (NFTs). The amyloid-oligomer hypothesis indicates that the buildup of toxic oligomers in vivo is likely to impair memory and synaptic function. Methods: In our study, a kind of novel recombinant chimeric 12×(Aβ1-15-Th) antigen was developed as 12-mer Aβ1-42-like assembly vaccine. We designed this 12×(Aβ1-15-Th) antigen to mimic the assembly states of Aβ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This study also suggests that the Aβ derivative, when used with an adjuvant suitable for humans, can reduce Aβ load and promote cognitive improvement without increasing vascular microbleeds compared to other Aβ antibody studies [3]. In 2021, Fang et al [15] reported a novel recombinant chimeric 12×(Aβ1-15-Th) antigen targeting the pathological confirmation of Aβ oligomer for AD treatment. They tested the immunogenicity of the chimeric vaccine in C57/BL6 mice and demonstrated its efficacy in AD mice.…”
Section: Immunotherapy Targeting Amyloid βmentioning
confidence: 76%
See 1 more Smart Citation
“…This study also suggests that the Aβ derivative, when used with an adjuvant suitable for humans, can reduce Aβ load and promote cognitive improvement without increasing vascular microbleeds compared to other Aβ antibody studies [3]. In 2021, Fang et al [15] reported a novel recombinant chimeric 12×(Aβ1-15-Th) antigen targeting the pathological confirmation of Aβ oligomer for AD treatment. They tested the immunogenicity of the chimeric vaccine in C57/BL6 mice and demonstrated its efficacy in AD mice.…”
Section: Immunotherapy Targeting Amyloid βmentioning
confidence: 76%
“…They tested the immunogenicity of the chimeric vaccine in C57/BL6 mice and demonstrated its efficacy in AD mice. The results showed that the chimeric vaccine showed a noticeable neuroprotective effect by reducing the levels of soluble Aβ oligomers and soluble Aβ in the brain, suggesting that the chimeric vaccine is a good candidate for AD prevention [15]. ABvac40 is an active vaccine against the C-terminal end of Aβ40, and an ongoing Phase II clinical trial is needed to explore the clinical efficacy of ABvac40 [30].…”
Section: Immunotherapy Targeting Amyloid βmentioning
confidence: 99%